Binary Solvent System for Extraction of Cathode Material From Spent Li-ion Batteries (Dhaka University Journal of Science, 2022)
An effective method of water and carbon tetrachloride (CCl4) system has been studied to recover metals ions from spent Li-ion battery cathode materials. Leaching of HCl and HCl + H2O2 has been applied individually to dissolve the collected cathode materials. Metal ions dissolved in HCl and HCl + H2O2 has been treated separately with a solution of hexadecyl amine in CCl4. The formation of metal ions-hexadecyl amine complex has been confirmed from UV-visible spectroscopy. Recovery of metals from the produced complex has been carried out via filtration and calcination. The calcined materials has been characterized using Fourier transform infrared spectroscopy (FT-IR),field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS) andpowder x-ray diffraction (XRD).Dhaka Univ. J. Sci. 69(3): 225-229, 2022 (June)